Model Reaksi Oksidasi Pvc Di Dalam Suspensi Kapur Pada Suhu Dan Tekanan Tinggi - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran(UI2P2) UGM, 2005)
ABSTRAK Modeling of the oxidation of polyvinyl chloride (PVC) at high pressure and temperature in calcium hydroxide Ca(OH)2, suspension has been studied. A mixture of plastics of PVC, Ca(OH)2 powder and aquadest were heated in the autoclave, and oxygen was introduced into the autoclave at the desired pressure. Pressure and temperature were maintained constant during the oxidation process, which was run for 2 to 6 hours. When the process finished, solid product was separated from the liquid one. Oxalic yield was determined in the solid product, and the liquid was analyzed its chloride content. The ranges of 'temperature and pressure investigated were from 200 to 250Â°C and from 35 to 55 atm, respectively. The results showed that the formation of oxalic acid and chloride increased with increase in the reaction time, temperature and pressure. However, at high pressure, temperature and longer reaction time, the yield of oxalic acid started slightly decreasing. Evaluation of the model showed that reaction of oxalic acid with Ca(OH)., took place very fast. The proposed- model for the reaction of dehydrochlorination and oxidation fits very well with the experimental data.